Ocimum basilicum Essential Oil Modulates Hematotoxicity, Oxidative Stress, DNA Damage, and Cell Cycle Arrest Induced by β-cyfluthrin in Rat Liver - Jebur, Ali B.; El-Sayed, Raghda A.; El-Demerdash, Fatma M. (Frontiers in Pharmacology, 2022)
Pesticides are used in large quantities infrequently, resulting in environmental damage and health issues. The goal of this study was to explore the ameliorating potential of Ocimum basilicum (Basil) leaves essential oil against the harmful effects of β-cyfluthrin in rat liver. Male Wistar rats were classified at random into four groups; control (corn oil), basil leaves essential oil (BEO, 3 ml/kg), β-cyfluthrin (β-Cyf; 15 mg/kg BW, 1/25 LD50), and BEO plus β-Cyf, respectively. Rats were given their respective doses orally for one month daily. Results revealed that BEO yielded 6.32 mg/g with 33 identified components, representing 97% of the total oil. BEO implicated a considerable level of total phenolic contents, DPPH radical scavenging capacity, ABTS activity, and FRAP. The treatment of β-Cyf dramatically elevated lipid peroxidation (LPO), protein oxidation (PC, AOPP, and HYP), and considerably reduced enzymatic (SOD, CAT, GPx, GR, GST) and non-enzymatic (GSH) antioxidants. After β-Cyf treatment, hematological parameters, body and liver weights, enzyme activity (AST, ALT, ALP, and LDH), and protein levels were all considerably affected. Additionally, β-Cyf induced higher levels of pro-inflammatory (TNF-α, IL-6) genes, as well as enhanced DNA damage and cell cycle arrest in the G0/G1 phase of liver cells. Furthermore, rats given BEO then intoxicated with β-Cyf showed substantial changes in the majority of the parameters tested. Finally, BEO was showed to have high antioxidant efficacy in combating β-Cyf toxicity because of its high phenolic content.